How much information is 'reasonable'? A qualitative interview study of the prescribing practices of palliative care professionals. (September 2022) - Dumble, Katie; Driessen, Annelieke; Borgstrom, Erica; Martin, Jonathan; Yardley, Sarah; Cohn, Simon
Background: Prescribing clinicians have to negotiate ambiguities around information provision and consent for medications on a daily basis, despite the availability of professional guidance. Aim: This study aims to explore some of the many factors prescribing clinicians in the United Kingdom take into account when deciding what information to give to patients about medication choices, and when. Design: In depth face-to-face interviews, utilising both a hypothetical scenario and semi-structured prompts, were conducted in order to elicit extended reflections on how clinicians individually work through such dilemmas and make decisions. Setting/participants: Ten prescribing clinicians (doctors and nurses) from a large combined team of National Health Service (NHS) secondary and community palliative care providers in England. Results: Palliative care staff regularly face choices about information provision in prescribing discussions, in particular when considering whether information might increase distress. Participants presented three overlapping framings that helped them assess the range of factors that could potentially be taken into account; (1) assessing the individual patient, (2) tailoring the provision of information and (3) jointly forming a plan. Conclusions: Information provision about medication choices and effects is a demanding, ongoing process, requiring nuanced judgements that constitute an unacknowledged yet significant aspect of clinical workload. Although current medical guidelines allow clinical discretion about information provision, this can leave individual clinicians feeling vulnerable. Further evolution of guidelines needs to establish a more sophisticated way to acknowledge professional and legal requirements, whilst also promoting professional autonomy and judgement.